Emotions, Emotional Intelligence and Professional Practice in Caring Professions - Habibie Bte Hj Ibrahim; Norhamidah Jarimal; Nurul Hudani Md Nawi; Puteri Hayati Megat (Asian Social Work Journal, 2018)
This paper based on literature review relates to emotions, emotional intelligence (EI) and their contributions to working relationships and decision-making processes are explored, particularly in social work settings. Little research has been conducted regarding emotion and Emotional Intelligence in the social work context. However, other caring professions such as health and nursing placed great emphasis on the importance of EI in their practice. Illness and healing processes occur within the context of relationships, and relationships are important frameworks for conceptualizing health care. This paper therefore aims to reveal the potential contributions of EI to working relationships with clients and decision-making processes in social work. This paper may provide some useful information for individuals and organizations as to how they can benefit from such contributions in order to develop more effective social work practices.